(untitled) (Journal of Basic and Applied Research in Biomedicine, 2022)
Culture influences people of a certain region leading to behavioral norms that not only affect people on an individual level but also rather affects the interrelations among them. In this article the author explores how culture might shape or influence the leader as well as the interrelation between the leader and his subordinates.The author argues that in order to adequately understand a given leader’s attributes, these should be examined in terms of a specific structural context across cultures. Thus, there is a growing need for understanding the way in which leadership enacted in various cultures and that is the amain purpose of this review.